On the Tree-Cutting Problem under Interest Rate and Forest Value Uncertainty - Luis H. R. Alvarez; Erkki Koskela (Center for Economic Studies and ifo Institute (CESifo), 2003)
The current literature on optimal forest rotation makes the unrealistic assumption of constant interest rate though harvesting decisions of forest stands are typically subject to long time horizons. We apply the Wicksellian single rotation framework to cover the unexplored case of variable and stochastic interest rate. By modelling the stochastic interest rate according to the Cox-Ingersoll-Ross model and the forest value as a geometric Brownian motion we provide an explicit solution for the Wicksellian single rotation problem and show that increased interest rate volatility increases the optimal exercise threshold of the irreversible harvesting opportunity and thereby prolongs the optimal rotation period. Numerical illustration indicates that the optimal threshold becomes higher at an increasing rate.
Keywords: 330; forest rotation; optimal stopping; stochastic interest rates